Universities in the Marketplace : The Commercialization of Higher Education - Bok, Derek Curtis (Book collections on Project MUSE., 2005)
Is everything in a university for sale if the price is right? In this book, one of America's leading educators cautions that the answer is all too often "yes." Taking the first comprehensive look at the growing commercialization of our academic institutions, Derek Bok probes the efforts on campus to profit financially not only from athletics but increasingly, from education and research as well. He shows how such ventures are undermining core academic values and what universities can do to limit the damage.Commercialization has many causes, but it could never have grown to its present state ha.